On paranormed λ-sequence spaces of non-absolute type - Karakaya, Vatan; Noman, Abdullah K.; Polat, Harun (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this work, we introduce some new generalized sequence spaces related to the spaces l(infinity)(p), c(p) and c(0)(p). Furthermore, we investigate some topological properties such as the completeness and the isomorphism, and we also give some inclusion relations among these sequence spaces. In addition, we compute the alpha-, beta- and gamma- duals of these spaces, and characterize certain matrix transformations on these sequence spaces. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Paranormed sequence space; alpha-, beta-, and gamma-duals; Weighted mean; lambda-sequence spaces; Matrix mapping; MATRIX TRANSFORMATIONS; EULER; Computer Science; Mathematics